The relationship of arm muscle strength, limb muscle explosive and movement coordination with swimming speed bracelet on students of physical education, health and recreation - Ikhwani, Yudi (International Journal for Educational and Vocational Studies, 2021)
This study aims to determined the relationship arm muscle strength, limb muscle explosive and movement coordination with coordination with swimming speed bracelet on students PENJASKESREK at Serambi Mekkah University. The population in this studied were all student PENJASKESREK at Serambi Mekkah University. Based on the purposive sampling technique, the samples totaling 30 students who had passed the T.P. Basic Swimming and T.P. Advanced Swimming. Based on the results of data analysis, it was found that arm muscle strength gave a relationship of 0.52 to the speed of breaststroke swimming in students, limb muscle explosive gave a relationship of 0.44 to the speed of breaststroke swimming to students, movement coordination gave a relationship of 0,42 with the speed of breaststroke swimming to students. The concluded that arm muscle strength, limb muscle explosive and movement coordination were related by 0.79 with the breaststroke swimming speed on Students at Serambi Mekkah University. So the hypothesis that the author proposed was accepted as true.